ANALISIS PENERAPAN PROSEDUR PEMOTONGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 23 ATAS JASA PADA PT. DANA TABUNGAN DAN ASURANSI PEGAWAI NEGERI (PERSERO) KANTOR CABANG MANADO - Wiyadi, Nadia K.; Sondakh, Jullie J.; Pinatik, Sherly (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Tax is one of the revenue sources of the largest country in Indonesian. A function of tax namely can be used to finance all government spending, in terms of development and activities that pertaining to the interests and prosperity the country. One source of country revenues is income tax. This study aims to analysis the application of the procedure of cutting, payment and reporting Income Tax Article 23 for services to PT. Savings Accounts and Insurance Civil Servants (Persero) Branch Offices Manado is it in accordance with the law number 36/2008 who set about income tax in Indonesian. The method of analysis that used in this research analytics object, cutting the calculation and payment and reporting and analysis. And the kind of research used in this research was the qualitative study descriptive. The results of research obtained (1) Objects income tax article 23 all have applied in accordance with the provisions the act of income tax article 23 (2) The calculation when tested, there is some object which had not yet in accordance with the provisions of article 23 (3) The process of payment and reporting income tax is in line with provisions of article 23. Keywords : Analysis, Procedure, Income Tax, Services